A mechanistic study of the temperature dependence of the stress corrosion crack growth rate in SUS316 stainless steels exposed to PWR primary water. (1st August 2016) - Meisnar, Martina; Vilalta-Clemente, Arantxa; Moody, Michael; Arioka, Koji; Lozano-Perez, Sergio
Abstract: Complementary analytical transmission electron microscopy (TEM) and transmission Kikuchi diffraction (TKD) were used to study the influence of temperature on the crack growth rate (CGR) in SUS316 stainless steels. An Arrhenius-type temperature dependence of the CGR has been observed between 250 °C and 320 °C. However, stress corrosion cracking (SCC) CGRs were found to decrease between 320 °C and 360 °C, which cannot be explained in terms of a single operating mechanism. High-resolution characterization has produced direct evidence that the SCC CGR in SUS316 is subjected to, at least, two rate-controlling processes: thermally activated diffusion and mechanical response to external stress and internal strain. While diffusion of metallic and non-metallic species at the crack flanks are enhanced at higher temperatures (350 °C and 360 °C), mechanical response-based mechanisms appear to dominate at lower temperatures (320 °C and 340 °C). Higher strain concentrations and dislocation densities around the crack tip were found at low temperature, potentially leading to accelerated crack growth and a peak in the CGR at ∼320 °C. It is suggested that phenomena occurring near the crack tip can be potentially very different at high and low temperatures. Graphical abstract: